Nowy żar Kuźni bluźnierstw - Lam, Andrzej (Poznańskie Studia Polonistyczne. Seria Literacka, 2016)
The article discusses a collection of Karol Irzykowski’s aphorisms entitled Kuźnia bluźnierstw (The Forge of Blasphemy, 1911, printed as a book in 1913), its role against the trends of the times, especially Nietzsche’s philosophy and psychoanalysis, the importance of social rebellions, national uprisings and artistic revolutions (“blaspheming”, “bravado”, “pioneering”, audiacia civilis). In the subsequent part of the article, the author discusses the topicality of a critic’s theses in relation to the contemporary disputes over the content and the language of the argumentation. The author has placed pragmatism at the centre of the considerations, with special emphasis placed on intellectual and artistic deeds, antecedent awareness and its caricature i.e. usurpation. This is concisely put in the following aphorism: “Genuine faith feeds on lack of faith; it only lives because it is constantly restored”.